Perceived clinical and ethical impact of digital transformation in healthcare and research: A survey in the MENA region - Hasan, Hisham E.; Alzoubi, Karem H.; Khabour, Omar F.; Al-Delaimy, Wael K.; Goodman, Kenneth W. (PLOS ONE, 2025)
Background The shift toward digital medical records and communication represents a transformative change in healthcare practices and research. However, this transition is marked by challenges related to the ethics of digital health adoption in fragile and conflict-affected areas, particularly in areas where healthcare providers lack prior training and preparation. Objective To assess healthcare and research professionals’ adoption, attitudes, perceptions, and ethical considerations toward digital transformation in healthcare and research across the Middle East and North Africa (MENA) region. Methods A cross-sectional survey was conducted in 20 MENA countries involving 990 health professionals and researchers. Demographic data was collected, as well as questions related to the impact, attitudes, and ethics of digital health transformation. Data were analyzed using descriptive and inferential statistical methods to identify patterns and correlations between sociodemographic factors and responses. Results The results indicate that digital health transformation in the MENA region was perceived as limited to moderate across key domains, with relatively positive scores on attitudes and ethical considerations. While foundational technologies, such as electronic health records, show moderate adoption, other advanced tools remain underutilized. The study also revealed a significant lack of formal training in digital health (p < 0.001) despite high digital proficiency among participants (p < 0.001). However, ethical concerns were highlighted as key issues with strong support for enhanced bioethics literacy. These findings align with the Sustainable Development Goals (SDGs) and emphasize the need to develop inclusive policies, implement robust regulatory frameworks, create targeted educational programs, make infrastructure investments, and foster stakeholder collaboration to promote the ethical use of digital health technologies. Conclusion Digital transformation in healthcare and research is viewed positively across the MENA region, but significant gaps remain in adoption, training, and governance. Addressing these gaps will be essential to ensure safe, equitable, and sustainable digital health implementation.